CD4+CD25highCD127low Regulatory T Cells in Peripheral Blood Are Not an Independent Factor for Chronic Graft-versus-Host Disease after Allogeneic Stem Cell Transplantation - Jolanta B. Perz; Selma Gürel; Stefan O. Schonland; Ute Hegenbart; Anthony D. Ho; Peter Dreger (The Scientific World Journal)
Background. The therapeutic efficacy of allogeneic hemopoietic stem cell transplantation (HSCT) largely relies on the graft-versus-leukemia (GVL) effect. Uncontrolled graft-versus-host disease (GVHD) is a feared complication of HSCT. Regulatory T cells (Treg) are a subset of CD4+ T-helper cells believed to maintain tolerance after HSCT. It remains unclear whether low peripheral blood Treg have an impact on the risk for acute (aGVHD) and chronic GVHD (cGVHD). Methods. In this paper we enumerated the CD4+CD25highCD127low Treg in the peripheral blood of 84 patients after at least 150 days from HSCT and in 20 healthy age-matched controls. Results. Although similar mean lymphocyte counts were found in patients and controls, CD3+CD4+ T-cell counts were significantly lower in patients. Patients also had significantly lower Treg percentages among lymphocytes as compared to controls. Patients with cGVHD had even higher percentages of Treg if compared to patients without cGVHD. In multivariate analysis, Treg percentages were not an independent factor for cGVHD. Conclusions. This paper did not show a relation between deficient peripheral blood Treg and cGVHD, therefore cGVHD does not seem to occur as a result of peripheral Treg paucity.